Extraction Of Brazilin From Sappan Wood as a Natural Reagent for Borax Detection by Digital Imaging Analysis - Rismiarti, Zuri; Rahmat, Mamat; Nur Indra, Asep Iin; Syaindi, Amanda Afifah (Jurnal Kesehatan Prima, 2024)
The use of brazilien for borax detection is because the chemical properties of this compound are greatly influenced by pH which results in a change in the color of the brazilien. This compound gives an orange color at a pH range of 6-7 and yellow at an acidic pH, while at a pH range of 7-10 it gives a red color and at a pH >10 it gives a purplish red color. This research uses Brazilian extract from sappan wood for borax detection. By utilizing this compound extract, the use of chemical reagents for the detection of borax in food samples can be minimized. Apart from that, it can increase the added value of these crop commodities and can take advantage of the abundant natural resources in Indonesia. This research aims to develop a method that is accurate, simple and cheap and does not use special instruments to diagnose borax based on digital imaging, which includes extraction of brazilien from sappan wood using a maceration method using 96% ethanol solvent and water with a UV-Vis spectrophotometer, ratio optimization brazilin extract with boric acid, optimization of measurement time. The results of the research show that the solvent that provides optimum absorbance for brazilin extraction is water or distilled water, with a ratio of brazilin extract and boric acid of 1:1 and the measurement time is 5 minutes.